2020
DOI: 10.1093/ofid/ofaa457
|View full text |Cite
|
Sign up to set email alerts
|

Uncomplicated Staphylococcus aureus Bacteremia Treatment Duration and Outcomes at an Academic Medical Center

Abstract: We compared outcomes and clinical characteristics of uncomplicated Staphylococcus aureus bacteremia planned for a 14-day or >14-day course of intravenous antibiotics. Treatment failure was infrequent in both groups (0% and 5%, respectively). Catheter-associated deep vein thrombosis, immunosuppression, and valvular dysfunction were associated with a longer planned duration of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 11 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…In addition, there were clinical and statistically significant differences in basal characteristics between groups, which could have resulted in selection bias. In the study by Taupin et al , 22 there were no differences in variables such as age, sex, sensitivity to oxacillin, and community origin, but there were differences in terms of immunosuppression and the presence of valvular heart disease, which were greater in the long-course group. In the study by Chong et al , 23 no differences were found in both comparisons regarding age, sex, community origin, antibiotic treatment, MRSA isolation, and comorbidities such as diabetes mellitus (DM), immunosuppression, hemodialysis dependence, liver cirrhosis, prosthetic device, among others.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…In addition, there were clinical and statistically significant differences in basal characteristics between groups, which could have resulted in selection bias. In the study by Taupin et al , 22 there were no differences in variables such as age, sex, sensitivity to oxacillin, and community origin, but there were differences in terms of immunosuppression and the presence of valvular heart disease, which were greater in the long-course group. In the study by Chong et al , 23 no differences were found in both comparisons regarding age, sex, community origin, antibiotic treatment, MRSA isolation, and comorbidities such as diabetes mellitus (DM), immunosuppression, hemodialysis dependence, liver cirrhosis, prosthetic device, among others.…”
Section: Resultsmentioning
confidence: 85%
“…A total of 3146 individual studies were identified, of which 6 non-RCTs 22 27 with a total of 1700 patients were finally included. No RCTs met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, there is likely to be systematic difference in the clinical management of CRBI conditional on the organism type. The perception by clinicians that MSSA and MRSA CRBIs are associated with poorer outcomes may encourage clinicians to adopt a more aggressive strategy of hospital admission, prescription of a longer course of intravenous antibiotics (typically at least 14 days for uncomplicated Staphylococcus aureus bacteraemia 9 ) and prompt removal of vascular catheters, which is reflected in our study showing a greater likelihood of hospital admission and a shorter median time to catheter removal in patients with Gram positive CRBI 10 . Even though our study did not demonstrate a difference in the risk of metastatic infection and death from CRBI between organism types, it is noteworthy that almost 20% of CRBI required ICU admission, had evidence of metastatic infection or had died from CRBI.…”
Section: Discussionmentioning
confidence: 99%